2022
DOI: 10.3389/fmed.2022.983939
|View full text |Cite
|
Sign up to set email alerts
|

Vasculitis associated with VEXAS syndrome: A literature review

Abstract: Vasculitis is an inflammatory disorder of the blood vessels that causes damage to a wide variety of organs through tissue ischemia. Vasculitis is classified according to the size (large, medium, or small) of the blood vessels. In 2020, VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome, a novel autoinflammatory syndrome, was described. Somatic mutations in methionine-41 of UBA1, the major E1 enzyme that initiates ubiquitylation, are attributed to this disorder. This new disease entity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 82 publications
0
27
0
6
Order By: Relevance
“…Both patients had raised endothelial markers ICAM-1, VCAM-1, VWF:Ag, and glycoprotein 1B binding activity, with the presence of vasculitis in VEXAS syndrome in patient 2, suggesting evidence for ongoing endothelial dysfunction. In a recent literature review vascular inflammation with involvement of small, medium, and large vessels was identified 9 and in a report by Karadeniz et al of two patients with VEXAS syndrome there was severe thickening of the walls of large veins detected on Doppler ultrasound, suggestive of venulitis. 10…”
Section: Tablementioning
confidence: 98%
See 1 more Smart Citation
“…Both patients had raised endothelial markers ICAM-1, VCAM-1, VWF:Ag, and glycoprotein 1B binding activity, with the presence of vasculitis in VEXAS syndrome in patient 2, suggesting evidence for ongoing endothelial dysfunction. In a recent literature review vascular inflammation with involvement of small, medium, and large vessels was identified 9 and in a report by Karadeniz et al of two patients with VEXAS syndrome there was severe thickening of the walls of large veins detected on Doppler ultrasound, suggestive of venulitis. 10…”
Section: Tablementioning
confidence: 98%
“…8 Both patients had raised endothelial markers ICAM-1, VCAM-1, VWF:Ag, and glycoprotein 1B binding activity, with the presence of vasculitis in VEXAS syndrome in patient 2, suggesting evidence for ongoing endothelial dysfunction. In a recent literature review vascular inflammation with involvement of small, medium, and large vessels was identified 9 and in a report by Karadeniz et al of two patients with VEXAS syndrome there was severe thickening of the walls of large veins detected on Doppler ultrasound, suggestive of venulitis. 10 In summary, given the findings of inflammation, hypercoagulability and endothelial dysfunction, long-term anticoagulation treatment in VEXAS patients with known thrombosis, together with anti-inflammatory and immunosuppressive therapies, may provide an appropriate therapeutic approach to VEXAS syndrome.…”
mentioning
confidence: 98%
“…B. rezidivierende Polychondritis, Riesenzellarteriitis oder Sweet-Syndrom) erfüllten, durch die gleiche Mutation erklärt werden konnten. Das VEXAS-Syndrom kann neben einer Chondritis auch mit einer Vaskulitis von Gefäßen unterschiedlicher Größe einhergehen und zum Beispiel RZA, PAN oder Kleingefäßvaskulitiden (insbesondere leukozytoklastische Hautvaskulitis, in Einzelfällen auch GPA oder MPA) imitieren 75 76 .…”
Section: Imitatoren Von Vaskulitiden Unterschiedlicher ...unclassified
“…Ubiquitylation is essential for a variety of cellular processes, such as cell-cycle progression, deoxyribonucleic acid damage response, and immune signaling pathways. 10 Mutations in UBA1 lead to reduced ubiquitination and activation of autoimmune pathways, resulting in inflammatory manifestations. 1,2,13,15 X-Linked UBA1 is located on the X chromosome (Xp11.3) and can escape X chromosome inactivation.…”
Section: E1 Enzymementioning
confidence: 99%
“…Chest computed tomography demonstrated diffuse bilateral ground-glass opacities and pleural effusions. 1,10,22 Hematologic Aspects…”
Section: Lung Involvementmentioning
confidence: 99%